2013
DOI: 10.1074/jbc.m113.473785
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation Induces the CTHRC1 Protein and Drives Oral Cancer Cell Migration

Abstract: Background: Increased protein N-glycosylation and aberrant Wnt signaling are features of oral cancer. Results: Overexpression of pro-migratory protein CTHRC1 is due to hyperglycosylation and transcriptional activation by canonical Wnt. Conclusion: N-Glycosylation collaborates with canonical Wnt to induce CTHRC1 and drive OSCC cell migration. Significance: Elucidating how N-glycosylation impacts tumor-promoting proteins is critical to understand cancer development and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 42 publications
1
78
0
Order By: Relevance
“…In the presence of ligand Wnt3a/1/8, Wnt/β-catenin pathway will be activated, including Wnt-FZDs-Lrp5/6 complex which transduces signals to the cellular downstream and leads to accumulation of β-catenin in cytoplasm. The upregulated β-catenin translocates to nucleus and regulates a wide range of genes by binding to a series transcription factors such as TCF/LEF 20. There is scientific evidence suggesting that the biological effect of CTHRC1 on metastasis and proliferation of tumor cells is cross-linked with the canonical Wnt/β-catenin pathway.…”
Section: The Role Of Cthrc1 In Multi-signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of ligand Wnt3a/1/8, Wnt/β-catenin pathway will be activated, including Wnt-FZDs-Lrp5/6 complex which transduces signals to the cellular downstream and leads to accumulation of β-catenin in cytoplasm. The upregulated β-catenin translocates to nucleus and regulates a wide range of genes by binding to a series transcription factors such as TCF/LEF 20. There is scientific evidence suggesting that the biological effect of CTHRC1 on metastasis and proliferation of tumor cells is cross-linked with the canonical Wnt/β-catenin pathway.…”
Section: The Role Of Cthrc1 In Multi-signaling Pathwaysmentioning
confidence: 99%
“…Excavated molecular biology characterizations reveal that the expression level of CTHRC1 significantly correlates with transforming growth factor-β (TGF-β1) and promoter demethylation 13, 19. Furthermore, N-glycosylation may cooperate with canonical Wnt signaling pathways to intensify the overexpression of CTHRC1 and promote Oral squamous cell carcinoma (OSCC) metastasis 20.…”
Section: Introductionmentioning
confidence: 99%
“…Atypical glycosylation of cell surface carbohydrates has been reported to be associated with malignant transformation of oral epithelium (9), and protein-bound sugar levels were higher in plasma and tissue samples of oral cancer patients (10). A series of studies about dysregulation of the N-glycosylation-regulating gene, DPAGT1, drives oral cancer cell discohesion by inhibiting adhesion of E-cadherin through Wnt signaling pathway were reported (11)(12)(13). It was also found that the expression of Lewis y on EGFR promotes migration of oral cancer cells (14).…”
mentioning
confidence: 99%
“…Furthermore, abnormal glycosylation of cell surface proteins takes place during which normal cells progress to a malignant neoplastic state [1]. Thus, the modification of cell surface glycosylation is a characteristic of many cancer cells [24]. Many of the recently developed tumor markers are carbohydrate antigens.…”
mentioning
confidence: 99%